ANALISIS STRATEGI UNTUK MEMPERTAHANKAN PELANGGAN PRODUK KARET PADA CV ELNAM MANDIRI DI PORIS TANGERANG - Naomi Tesya Nofani; Mada Faisal Akbar (Journal of Research and Publication Innovation, 2025)
This study aims to analyze effective strategies for retaining customers of rubber products at CV Elnam Mandiri Poris Tangerang. The research adopts a qualitative approach using in-depth interview methods, involving the company's owner and several customers as respondents. Through these in-depth interviews, data were obtained regarding customers' perspectives and experiences, as well as the strategies implemented by the company to retain them. Subsequently, the collected data were analyzed using the SWOT method (Strengths, Weaknesses, Opportunities, Threats), which aims to identify and understand the strengths, weaknesses, opportunities, and threats faced by the company in the context of customer relationship management. The results of the SWOT analysis indicate that CV Elnam Mandiri possesses several strengths, such as high product quality and good customer relations, but also faces challenges in terms of increasing production capacity and price competition. Opportunities that can be leveraged include the growing market demand for rubber products, while threats come from fluctuations in raw material prices and intense competition in the industry. Based on these findings, the study suggests several strategies for customer retention, including improving customer service, developing new products, and implementing competitive pricing. These findings are expected to contribute to the long-term business strategy development of CV Elnam Mandiri and serve as a reference for other companies in the same industry.